Scientific Literacy Skills Of State High School Students In Singkawang City - Ari Sunandar; Srihanaty Srihanaty; Hanum Mukti Rahayu (Postgraduate, University of Mataram, 2022)
Scientific literacy research by the Program for International Student Assessment (PISA) in the period 2000-2015 shows that the scientific literacy ability of Indonesian students is at a low level. This study aims to determine the scientific literacy ability of state high school students in Singkawang City. The method used is descriptive qualitative. The research was conducted in two public high schools in Singkawang City, namely SMA 1 and SMA 2 Singkawang. The samples taken were 127 students selected based on the simple random sampling technique. The research instrument used was a scientific literacy test in multiple-choice questions consisting of the dimensions of context, knowledge and competence. The results showed that the average science literacy test scores of SMA 1 students in the context dimension were 38%, the knowledge dimension was 40%, and the competence dimension was 39% which were very low. SMA 2 has 40% context dimension, 41% knowledge dimension and 39% competency dimension, classified as very low. So it can be concluded that SMA 1 and SMA 2 Singkawang students have very low scientific literacy skills based on three dimensions of scientific literacy ability